Kajian perbandingan antara WAP dan i-Mode / Jetol Bolongkikit - Jetol , Bolongkikit (2005)
Over the last few years, mobile Internet has been a hot topic that been discussed almost all over the world particularly among telecommunication industrial players. However, this issue seems that it has not materialized into anything much else than mostly talk until the emergence of i-Mode technology in February 1999, in Japan. i-Mode popularity as a users’ choice which toppled WAP technology has been an eye-opener among the industrial players of mobile Internet service. This scenario caused a competition between both mobile Internet service technologies. The main objective of the dissertation is to study the comparisons of technical and non-technical aspect between i-Mode and WAP technologies. In order to achieve it, overall literature reviews on both technologies have been conducted to get better understand. Based on the study, the successful factors of i-Mode technology have been formulated. One of the main successful factors of i-Mode is the adoption of packet switching technology as data transmission technology. Besides that, the smart business model that based on “win-win situation” approach, use efficient billing system, offer simple but attractive services and contents, low price for mobile telephone set, adopt smart publicity, and dominant factor of NTT DoCoMo on Japan industrial telecommunication market have been playing a vital role in the success of i-Mode technology. All these factors have been combined as a strategy and integrated approach that contributed to the overall successful of i-Mode as a technology of mobile Internet service.